Waste To Electricity: Pengembangan Keterampilan Siswa dalam Mengolah Sampah Organik Menjadi Energi Listrik - Septiana Ambarwati; Henny Parida Hutapea; Ameilia Wahyu Banuwati; Sri Jangkung Laksono Sukardi (Jurnal Kabar Masyarakat, 2026)
Organic waste management in Sukoharjo Regency remains a challenge that requires educational efforts and innovative approaches from an early age. SMP Islam Al Azhar Cairo Sukoharjo has the potential to become a partner in fostering students’ awareness of waste management and renewable energy utilization. This community service program aimed to improve students’ knowledge and skills in converting organic waste into electricity through Microbial Fuel Cell (MFC) technology. The activity was conducted on July 31, 2026, involving students and teachers through lectures, discussions, demonstrations, MFC assembly practices, and evaluation using pre-test and post-test assessments. The results showed an improvement in participants’ understanding of organic waste management, renewable energy concepts, and the working principles of MFC technology. The analysis using the Normalized Gain (N-gain) method obtained a value of 0.76, categorized as effective. This activity provided practice-based learning experiences and has the potential to serve as a living laboratory model to support scientific literacy and environmental awareness in schools.